Unusual Tumours Hidden in Blind Eyes - Gupta, Smriti Nagpal; Goel, Ruchi; Saran, Ravindra Kumar; Rathie, Neha (Nepalese Journal of Ophthalmology, 2021)
Introduction: This case report describes 3 cases of unsuspected neoplasms in previously blind eyes, with recent onset pain. Cases and observations: Case 1: Female with pain, redness in the non-seeing right eye (R/E) for two months. R/E had total cataract, low intraocular pressure and a well-defined globular mass lesion at the posterior pole, seen on ultrasound. Enucleation with an implant was done. Histopathology clinched the diagnosis of choroidal melanoma. Case 2: A 20-year male, developed pain, redness in left eye (L/E) for two months. L/E was blind since childhood, secondary to trauma. The patient underwent enucleation and detailed histopathological examination and immunohistochemistry supported a diagnosis of ependymoma with vascular malformation. Case 3: A 24-year male with pain, redness in L/E for six months, with decrease in size of eyeball. L/E had low vision since childhood. On examination, L/E was phthisical with diffuse conjunctival congestion, band-shaped keratopathy, cataract, and neovascularization of iris. Imaging revealed a small distorted globe with highly reflective mass along the posterior pole. Histopathology of the enucleated specimen confirmed the diagnosis of choroidal osteoma, with gliosis of the adjacent RPE. Conclusion: In the management of a painful blind eye, it is extremely important to rule out an intraocular malignancy, particularly in patients with recent onset of pain.